2019
DOI: 10.21070/picecrs.v2i1.2399
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality: Solusi Pembelajaran IPA di Era Revolusi Industri 4.0

Abstract: Nowadays, the changes of the world are entering era of industrial revolution 4.0, which is all aspects human life depend on digital technology. Preparing qualified graduates, gaining to compete globally, mastering technological developments are important for learning especially for the future of education in Indonesia. Science is one of the subjects that is related to technology which includes aspects of products, processes, scientific attitudes, and applications. Science as a product in the form a body of kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 5 publications
0
15
0
6
Order By: Relevance
“…The usual faceto-face science learning (conventional) changed to online learning by involving distance-oriented technology. The results of research conducted by Atista and Kuswanto (2018), Maulana et al (2019), Solikhin et al (2018), Sahida and Zarvianti (2019) showed that the urgency of online learning in the era of the industrial revolution 4.0 provides color in the education world.…”
Section: Introductionmentioning
confidence: 99%
“…The usual faceto-face science learning (conventional) changed to online learning by involving distance-oriented technology. The results of research conducted by Atista and Kuswanto (2018), Maulana et al (2019), Solikhin et al (2018), Sahida and Zarvianti (2019) showed that the urgency of online learning in the era of the industrial revolution 4.0 provides color in the education world.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu pemanfaatan kecanggihan teknologi pada aspek pendidikan dapat dilihat dari berbagai penggunaan alat dan media pembelajaran. (Maulana et al, 2019) menyebutkan perkembangan tersebut ditandai dengan penggunaan media yang berbasis teknlogi digital dalam proses pembelajaran yang dapat menembus ruang dan waktu. Fenomena ini terjadi pada semua jenjang pendidikan mulai dari pendidikan anak usia dini sampai perguruan tinggi.…”
Section: Pendahuluanunclassified
“…PENDAHULUAN Kualitas pendidikan merupakan syarat mutlak untuk menghasilkan sumber daya manusia yang andal yang akan menjadi generasi penerus pembentuk masa depan bangsa (Maulana et al, 2019). It cannot be distinguished from the position of the principal, in which the main person plays a leading role in an educational institution.…”
Section: Aunclassified